ON SOME FEATURES OF THE SPATIAL AND TEMPORAL STRUCTURE IN V. RASPUTIN’S SHORT NOVEL “FAREWELL TO MATYORA”. - MKRTCHYAN, MARIANNA (Bulletin of Yerevan University H: Russian Philology, 2021)
The subject of the article is the chronotope in V. Rasputin’s “Farewell to Matyora”. The time in this short novel is analyzed from the point of view of cyclical renewal in nature that lies in the core of the “village” archetype. The time perception of the characters is presented within the frames of two contrasting types of consciousness – archaic and historical. The meaning of the spatial elements of the text is analyzed from the point of their mythopoetical Meaning.
Keywords: “Farewell to Matyora”, chronotope, “village” archetype, mythopoetical analysis, cyclic view of time